Activity-dependent serotonergic excitation of callosal projection neurons in the mouse prefrontal cortex - Stephens, Emily K.; Avesar, Daniel; Gulledge, Allan T. (Frontiers in Neural Circuits, 2014)
Layer 5 pyramidal neurons (L5PNs) in the mouse prefrontal cortex respond to serotonin (5-HT) according to their long-distance axonal projections; 5-HT1A (1A) receptors mediate inhibitory responses in corticopontine (CPn) L5PNs, while 5-HT2A (2A) receptors can enhance action potential (AP) output in callosal/commissural (COM) L5PNs, either directly (in “COM-excited” neurons), or following brief 1A-mediated inhibition (in “COM-biphasic” neurons). Here we compare the impact of 5-HT on the excitability of CPn and COM L5PNs experiencing variable excitatory drive produced by current injection (DC current or simulated synaptic current) or with exogenous glutamate. 5-HT delivered at resting membrane potentials, or paired with subthreshold depolarizing input, hyperpolarized CPn and COM-biphasic L5PNs and failed to promote AP generation in COM-excited L5PNs. Conversely, when paired with suprathreshold excitatory drive generating multiple APs, 5-HT suppressed AP output in CPn L5PNs, enhanced AP generation in COM-excited L5PNs, and generated variable responses in COM-biphasic L5PNs. While COM-excited neurons failed to respond to 5-HT in the presence of a 2A receptor antagonist, 32% of CPn neurons exhibited 2A-dependent excitation following blockade of 1A receptors. The presence of pharmacologically revealed 2A receptors in CPn L5PNs was correlated with the duration of 1A-mediated inhibition, yet biphasic excitatory responses to 5-HT were never observed, even when 5-HT was paired with strong excitatory drive. Our results suggest that 2A receptors selectively amplify the output of COM L5PNs experiencing suprathreshold excitatory drive, while shaping the duration of 1A-mediated inhibition in a subset of CPn L5PNs. Activity-dependent serotonergic excitation of COM L5PNs, combined with 1A-mediated inhibition of CPn and COM-biphasic L5PNs, may facilitate executive function by focusing network activity within cortical circuits subserving the most appropriate behavioral output.